Experimental study on the microbial plankton community in a South American wetland (Lower Paraná River Basin) and the effect of the light deficiency due to the floating macrophytes - Sinistro, R. (2006)
An experimental study using microcosms was conducted in a South American wetland, Lower Paraná River Basin (Argentina), to analyse the structure of the components of the microbial plankton community and the influence of the light deficiency due to floating macrophytes on this community. Two experiments were run under different light conditions; the decrease of the light penetration due to floating macrophytes was simulated using different nylon mesh covers that resembled natural conditions in the lake. These studies revealed that the light deficiency favoured the replacement of obligate autotrophs by mixotrophic and heterotrophic organisms. Abundances of strictly autotrophic algae along the experiments responded to the light gradient, being maximum in the flasks without cover. Heterotrophic nanoflagellates (HNF) and ciliates increased in the microcosms, probably favoured by the high food availability (picoplankton) and the lack of their predators (zooplankton). The increase of ciliates was higher in the microcosms with more light. In the first experiment, the picoplankton fraction strongly decreased after 24 h in the flasks that included all their potential predators, thus suggesting a grazing pressure on this fraction. Grazing experiments performed with fluorescent-labelled bacteria (FLB) revealed that two Cryptomonas species, which are frequent in the lake (Cryptomonas erosa and Cryptomonas marssonii), can ingest bacteria. © The Author 2006. Published by Oxford University Press. All rights reserved.